Analisis Nilai-Nilai Pendidikan Karakter Islami Dalam Kegiatan Amil Zakat Fitrah (Studi Kasus di MA Al-Ihsan Kelas X IPS ) - Lestari, Retno Dwi; Afidah, Nurul; Roziqin, Muhamad Khoirur (JoEMS (Journal of Education and Management Studies), 2024)
The research was carried out aimed to find out how much the application of character education is the responsibility of students towards the surrounding community through the management of corpse learning activities. This research method uses field research, which is qualitative in nature, namely research data procedures that produce descriptive data in the form of written or oral words from teachers and students tending to be analyzed. The results of the study are the first character at school, the second is Learning zakat chapters which are acted on in amil zakat activities in 10th grade IPS MA Al-Ihsan Kalikejambon, thirdly Islamic Characters are found in amil zakat activities. Various types of Islamic characters that must be fulfilled by students in amil zakat activities including The nature of honesty, patience, fairness, sincerity, etc. In learning the chapter on zakat in class students are encouraged to know the intention of zakat, the intention to receive zakat, those who are obliged to pay zakat and those who receive zakat. In practice, students make an amil zakat pania where they collect all zakat from students and then give it to the surrounding community who are obliged to receive the remaining zakat at the mosque to be given to people who are obliged to receive zakat in the Kalikejambon village.